Demokratisasi Kedaulatan Rakyat Dalam Pemilihan Kepala Daerah Serentak Tahun 2024 - Teguh Wicaksono (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Article 1 paragraph 2 of the 1945 Constitution of the Republic of Indonesia states that sovereignty is in the hands of the people. In the concept of a democratic state, the people have the sovereignty to choose state leaders to realize the ideals of the Indonesian state, one of which is to educate the nation's life and prosper its people. Elections and Pilkada are the main gateways for implementing sovereignty as mandated by the Constitution. However, the implementation of elections and regional elections which are often marred by the many frauds and deviations in practice makes the existence of the people's sovereignty questioned. The legal issues studied in this study are realizing people's sovereignty in regional head elections as well as the concept of regional head elections in a democratic country. The results of the research show that the new people's sovereignty will really be realized when the people are free in choosing, the regional election organizers maintain neutrality so that the regional elections are far from fraudulent in short true sovereignty will be realized if the principle of fairness and justice is successfully implemented.